Exploration of Mental Health in Children Victims of Bullying - Herman; Mohammad Fikri; Purwaty (Journal of Health and Nutrition Research, 2023)
This study aims to explore the mental health of bullying victims at SDN 3 Palu. This type of research is qualitative research with a case study approach. The research informants were 9 people based on purposive sampling technique. Data management using matrix techniques. The results showed that physical and non-physical bullying experienced by the victim caused thoughts of a negative self-concept, thoughts of hatred towards the perpetrator, and delusions/hallucinations due to trauma, so that the victim felt a threat. Conflict motives and control are carried out by communicating the events experienced, avoiding the perpetrator, and tend to remain silent when experiencing bullying, the victim feels unable to solve the problem on his own. Informants have less social interaction because their friendship is unhappy and do not feel calm when they are at school even though they have received support from their closest people. The emotions possessed by the informants were in the form of frequent crying, anger, and fear for no apparent reason as well as thinking disorders that disrupted daily activities. The advice given is that the school and parents should give attention and in-depth guidance to victims and perpetrators of bullying, present an anti-bullying program, and examine variable aspects from the point of view of teachers and perpetrators